PENGARUH KERJASAMA TIM DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP PRODUKTIVITAS KARYAWAN DI PT. ARROW CHAIN MANAGEMENT LOGISTICS CABANG PANDEGLANG - Komarudin, Komarudin; Aprilianti, Pipit (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
The success of an organization or institution in achieving its goals cannot be separated from the human resources it has. There are important factors related to human resources that are influential to improve and develop a company, one of which is employee productivity. Factors that can affect productivity include teamwork and democratic leadership styles. This study aims to determine the influence of teamwork and democratic leadership style on employee productivity at PT. Arrow Chain Management Logistics Pandeglang - Banten. This study uses a correlational quantitative method. The sampling technique used was the probability sampling method  and used a saturated sample with a population of 33 respondents, where the entire population was used as a sample. Data sources are obtained from primary data by distributing questionnaires and secondary data with documentation. This research was processed using smartPLS version 4.0.9.4. The results of the calculation of teamwork on employee productivity have a path coefficient of 0.266 with a t-statistical value of 4.082 and a significance value of p-value of 0.000 (<0.05). This value is greater than the t-table (1.96), which shows that the teamwork variable has a significant influence on employee productivity. The results of the calculation of democratic leadership style on employee productivity showed a path coefficient of 0.790 with a t-statistical value of 15.256 and a p-value significance of 0.000 (<0.05), which shows that the variable of democratic leadership style has a significant effect on employee productivity. In this study, it can be concluded that teamwork and democratic leadership style together have a significant influence on work productivity, which means that teamwork and democratic leadership style are two important factors that can affect employee productivity